2021
DOI: 10.1002/anie.202102601
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Assemblies of Thiophosphopeptides Instantly Target Golgi Apparatus and Selectively Kill Cancer Cells**

Abstract: Changing an oxygen atom of the phosphoester bond in phosphopeptides by a sulfur atom enables instantly targeting Golgi apparatus (GA) and selectively killing cancer cells by enzymatic self-assembly. Specifically, conjugating cysteamine S-phosphate to the C-terminal of a self-assembling peptide generates a thiophosphopeptide. Being a substrate of alkaline phosphatase (ALP), the thiophosphopeptide undergoes rapid ALP-catalyzed dephosphorylation to form a thiopeptide that self-assembles. The thiophosphopeptide en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 60 publications
4
62
0
Order By: Relevance
“…Although the furin‐triggered localized condensation was previously developed and enables the visualization of GA in a living cell, [68] GA‐targeting EISA for cancer inhibition was still limited. However, it is recently demonstrated that enzymatic assemblies of thiophosphopeptides ( 26 ) instantly accumulate in GA, allowing the selective HeLa inhibition (Figure 6c) [69] . The previous reports already revealed that cysteine‐rich proteins are enriched in GA [70] and a high level of oxidation occurs in GA membrane [71] .…”
Section: Representative Applications Of Eisamentioning
confidence: 94%
See 1 more Smart Citation
“…Although the furin‐triggered localized condensation was previously developed and enables the visualization of GA in a living cell, [68] GA‐targeting EISA for cancer inhibition was still limited. However, it is recently demonstrated that enzymatic assemblies of thiophosphopeptides ( 26 ) instantly accumulate in GA, allowing the selective HeLa inhibition (Figure 6c) [69] . The previous reports already revealed that cysteine‐rich proteins are enriched in GA [70] and a high level of oxidation occurs in GA membrane [71] .…”
Section: Representative Applications Of Eisamentioning
confidence: 94%
“…However, it is recently demonstrated that enzymatic assemblies of thiophosphopeptides (26) in- stantly accumulate in GA, allowing the selective HeLa inhibition (Figure 6c). [69] The previous reports already revealed that cysteine-rich proteins are enriched in GA [70] and a high level of oxidation occurs in GA membrane. [71] Based on these facts, the mechanism for GA targeting was proposed that (i) the 26, uptaken by a HeLa cell, is converted to 27 by the rapid dephosphorylation in GA, (ii) the 27, containing the thiol group, takes part in the self-assembly, (iii) the thiol group of the assemblies forms the disulfide bonds with the cysteine-rich proteins in GA, leading to the accumulation of the cytotoxic assemblies in GA. As the result, the IC 50 value is drastically reduced to about 3 μM.…”
Section: Subcellular Eisamentioning
confidence: 99%
“…To reactivate the suppressed immune response, immune cell epitopes and/or immune checkpoint inhibitors were conjugated with SAPs (Black et al., 2012 ; Li et al., 2021 ). Cytotoxic peptides conjugate SAPs (Standley et al., 2010 ; Toft et al., 2012 ), and self-assemblies of peptides induced by enzyme or pH in targeted organelle are lethal to cancer cells (Feng et al., 2018 ; Tan et al., 2021 ). To enhance the potential of photodynamic therapy (PDT), SAPs were conjugated with targeting peptide epitopes and photosensitizers (PSs) (Li et al., 2018c ; Tian et al., 2021 ).…”
Section: Recent Developments In Peptides-based Nano-cargosmentioning
confidence: 99%
“…Based on this structure, a considerable number of studies have investigated the physical properties (enzyme-catalyzed hydrogelation or supramolecular structural transformation) [62,70] and biological properties (cell viability, biostability, and cell-selective growth inhibition) [43,62] of the naphthylacetyl N-terminal-capped phosphopeptides. These studies have produced a variety of phosphopeptides that selectively inhibit cancer cells [38,64,65,71,72]. Encouraged by the results from the naphthylacetyl capped phosphopeptides, we decided to use multiple N-methylpyrroles, as the heteroaromatic analog of naphthyl, to cap the N-terminal of phosphopeptides for EISA.…”
Section: Molecular Designmentioning
confidence: 99%
“…One of the most explored EISA processes is the use of alkaline phosphatase (ALP) to convert the micelles made of phosphopeptides to the nanofibers of peptides via enzymatic dephosphorylation [20,60]. While ALP-catalyzed EISA has received considerable exploration, the structures of the peptide substrates mainly have centered on naphthylacetyl-capped phosphopeptides (e.g., Nap-ff p y (1)) [36,[61][62][63][64][65][66]. Considering naphthyl is an aromatic group, we decided to explore other aromatic N-terminal capping groups, such as heteroaromatic, N-terminal capping groups of phosphopeptides for EISA because they receive little exploration [67].…”
Section: Introductionmentioning
confidence: 99%